2020
DOI: 10.3390/ijms21249477
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal Antibodies and Airway Diseases

Abstract: Monoclonal antibodies, biologics, are a relatively new treatment option for severe chronic airway diseases, asthma, allergic rhinitis, and chronic rhinosinusitis (CRS). In this review, we focus on the physiological and pathomechanisms of monoclonal antibodies, and we present recent study results regarding their use as a therapeutic option against severe airway diseases. Airway mucosa acts as a relative barrier, modulating antigenic stimulation and responding to environmental pathogen exposure with a specific, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 164 publications
0
12
0
Order By: Relevance
“…Only two were undergoing biological anti-immunoglobulin-E (IgE) treatment for asthma, and none were undergoing biological treatment for nasal polyposis, despite recurrent courses of corticosteroids and numerous surgical procedures for nasal polyp control. Biological monoclonal antibody medication for severe nasal polyposis is a relatively recent therapeutic option ( 23 ), and the timing of the data collection is likely to have played a part in the scarce usage of biological medication in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Only two were undergoing biological anti-immunoglobulin-E (IgE) treatment for asthma, and none were undergoing biological treatment for nasal polyposis, despite recurrent courses of corticosteroids and numerous surgical procedures for nasal polyp control. Biological monoclonal antibody medication for severe nasal polyposis is a relatively recent therapeutic option ( 23 ), and the timing of the data collection is likely to have played a part in the scarce usage of biological medication in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of clinical implications, our findings may prove relevant to patient counselling, following up on and planning treatment, such as that of biological therapy [12]. However, validation studies for these results remain necessary.…”
Section: Plos Onementioning
confidence: 74%
“…The success rates for initial ESS range from 76% to 98% [8,9]. The early identification of CRS recurrence risk following ESS is cost-effective [10,11], helping to correctly target treatment [12] and prevent permanent tissue changes [1].…”
Section: Introductionmentioning
confidence: 99%
“…Public medical care covers over 90% of our operations 56 thus minimizing possibility of bias due to loss of follow up, yet we acknowledge that some individual patients with recurrence may have sought treatment elsewhere. Despite these limitations, we found that intelligent data analysis is feasible to obtain individual probability of revision ESS, and thus could help in informing discussions and decision making of advanced therapy, such as biologicals 57 .…”
Section: Discussionmentioning
confidence: 99%